Observation and control of maximal Chern numbers in a chiral topological semimetal - Schroter, Niels B. M.; Stolz, Samuel; Manna, Kaustuv; De Juan, Fernando; Vergniory, Maia G.; Krieger, Jonas A.; Pei, Ding; Schmitt, Thorsten; Dudin, Pavel; Kim, Timur K.; Cacho, Cephise; Bradlyn, Barry; et al. (Science, 2020)
Topological semimetals feature protected nodal band degeneracies characterized by a topological invariant known as the Chern number (C). Nodal band crossings with linear dispersion are expected to have at most |C| = 4, which sets an upper limit to the magnitude of many topological phenomena in these materials. Here, we show that the chiral crystal palladium gallium (PdGa) displays multifold band crossings, which are connected by exactly four surface Fermi arcs, thus proving that they carry the maximal Chern number magnitude of 4. By comparing two enantiomers, we observe a reversal of their Fermi-arc velocities, which demonstrates that the handedness of chiral crystals can be used to control the sign of their Chern numbers.
CRIS-Team Scopus Importer:2022-04-14